PENGARUH KOMPETENSI DAN INSENTIF TERHADAP KINERJA KARYAWAN - Mansyur, Syahrul; Maedina, Rosida (Jurnal Metaverse ADPERTISI, 2025)
The purpose of this study will be to analyze the relationship between competencies and incentives on employee performance. This type of research is quantitative. Population is the overall subject of the study. All employees of PT Semen Tonasa (Persero) Tonasa IV unit staff became the population of this study totaling 102 people. The determination of the number of samples using the Slovin approach, a sample of 50 people was obtained. The data sources used in this study are primary data and secondary data. The questionnaire distribution technique uses a Likert scale. The data analysis method uses multiple regression analysis. The results of the study found that competence had a positive effect on employee performance partially. This means that if the employee's competence increases, the performance will also increase. Furthermore, incentives also have a positive effect on employee performance partially. This means that if incentives increase, employee performance will also increase.